AB0436 Persistence of Clinical Remission by a Decreased Treatment Regimen of 4 MG/KG Intravenous Tocilizumab: A Randomized Clinical Trial. (9th June 2015) - Giollo, A.; Viapiana, O.; Orsolini, G.; Liuzza, S.; Troplini, S.; Risoli, M.; Dal Forno, I.; Idolazzi, L.; Gatti, D.; Rossini, M.; Adami, S.
Abstract : Background: The aim of the Rheumatoid Arthritis (RA) treatment is the achievement of remission or low disease activity in the shortest possible time. The EULAR Task Force suggests that in cases of persistent remission, after tapering glucocorticoids, patients and physicians may decide together to titrate the dose of conventional synthetic disease-modifying antirheumatic drugs (DMARDs) or consider tapering biological DMARDs. Objectives: The objective of this study is to evaluate in RA patients on remission after a standard tocilizumab (TCZ) dose (8mg/kg/month) the persistence of remission by halving the dose. Methods: The patients in persistent (>1 year without flare) clinical remission (DAS28 <2.6) and with the absence of US signs of disease activity were included in this study. They were assigned consecutively (1: 1) to continue TCZ at a standard-dose regimen (8 mg/kg) or to 4 mg/kg reduced-dose regimen. Clinical and US evaluations were performed every 2 months in all patients. The clinical assessment included: anthropometric and demographic characteristics (age, sex, height, weight), disease duration, laboratory markers (Erythrocyte Sedimentation Rate [ESR], C –Reactive Protein [CRP], rheumatoid factor, Anti–citrullinated protein antibody [ACPA], complete blood count, liver and renal function tests), disease activity scores (DAS28-CRP). Results: Nineteen of the 26 RA patients treated with tocilizumab in our Unit met the first inclusion criteria for randomization, i.e.: persistent clinical remission (DAS28 <2.6). However, 4 of these patients had US signs of disease activity. The other 15 patients did not show any sign of US disease activity and were therefore assigned consecutively with a 1: 1 ratio to continue TCZ at a standard-dose regimen (8 mg/kg) or to 4 mg/kg reduced-dose regimen. No significant or relevant differences between the 2 groups of patients were observed. Over the 12 months of follow up the mean DAS28 values were very similar in patients who continued the standard 8mg/kg TCZ dose and in those who switched to a reduced dose of 4 mg/kg. In none of them a disease flare in terms of both DAS28 and US assessment was observed. Conclusions: For the tiny number of subjects and the relatively short follow up, we are not able to draw conclusions, but our results indicate that in patients with severe RA, unresponsive to anti-TNFα agents and achieving a full remission with TCZ treatment a dose tapering to 4 mg/kg may be considered, keeping in mind the positive consequences on the economic burden of therapy and that TCZ safety profile is dose dependent. Disclosure of Interest: None declared